2021
DOI: 10.1016/j.enbuild.2021.111346
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on higher education building energy use and implications for future education building energy studies

Abstract: Although COVID-19 has significantly changed the higher educational sector, there are few studies revealing how this pandemic has changed the energy use of higher education buildings. This study was conducted not only to disclose the energy use change under COVID-19 but also to identify the corresponding facilities management strategies for future learning and teaching delivery modes under virtual campuses. This study collected the energy use data of 122 buildings across five campuses in Griffith University, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…With the reopening of the economy, the numbers flipped from savings to overconsumption. In line with our study, and showing a decreasing tendency in energy consumption, is the Gui et al [34] research that states an energy consumption cut of around 24.88 kWh/m 2 on HVAC systems during the academic year at five campuses at Griffith University, Southeast Queensland, Australia. The results are due to the lockdowns and Queensland's "humid subtropical" climate classification (Köppen−Geiger Climate Classification subtype "Cfa"-Humid Subtropical Climate), showing an energy-saving trend in line with our study for "very hot" to "hot-humid" climates (Zone 1-A Haikou and 2-A Guangzhou).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With the reopening of the economy, the numbers flipped from savings to overconsumption. In line with our study, and showing a decreasing tendency in energy consumption, is the Gui et al [34] research that states an energy consumption cut of around 24.88 kWh/m 2 on HVAC systems during the academic year at five campuses at Griffith University, Southeast Queensland, Australia. The results are due to the lockdowns and Queensland's "humid subtropical" climate classification (Köppen−Geiger Climate Classification subtype "Cfa"-Humid Subtropical Climate), showing an energy-saving trend in line with our study for "very hot" to "hot-humid" climates (Zone 1-A Haikou and 2-A Guangzhou).…”
Section: Discussionsupporting
confidence: 92%
“…Natural gas faced even more significant cuts, achieving a yearly average of (−)7.31% to reduce heating and hot water consumption, which shows a contrasting tendency against the overconsumption claim. By the same token, Gui et al [34], in a report about the impact of COVID-19 on higher education building energy use and implications for future energy studies, reported a consumption cut of 9646.933 kWh, or around 24.88 kWh/m 2 , of energy use intensity (EUI) during the academic year (17 February 2020 to 21 February 2021, and from 18 February 2019 to 16 February 2020) on HVAC management by overseeing a sample of 122 buildings across five campuses at Griffith University, located in Southeast Queensland, Australia. On a wider scale, Wang et al [35], in their study on uncovering the impact of the COVID-19 pandemic on energy consumption between pandemic-free scenarios and actual electricity consumption in China, state that electricity has dropped by (−)29% due to the COVID-19 epidemic (January to August 2020) compared to the 2015 to 2019 period.…”
Section: Operation Guidelinesmentioning
confidence: 95%
“…Pelaksanaan pembelajaaran tentunnya harus terpaksa dilaksanakan dengan skenario pembelajaran daring. Penggunaan teknologi digital memungkinkan mahasiswa dan dosen berada di tempat yang berbeda selama pembelajaran (Gui et al, 2021). Seperti yang telah dicatat oleh WHO, salah satu dari pelajaran utama yang dipetik dari peristiwa kesehatan masyarakat utama abad ke-21 adalah bahwa Risk Communication And Community Engagement (RCCE) integral dari keberhasilan tanggapan terhadap kedaruratan kesehatan (WHO, 2017).…”
Section: Pendahuluanunclassified
“…Gaspar et al (2022) reported that the energy consumption in academic buildings was found to be clearly influenced by climatic conditions, particularly in winter. Meanwhile, a study by Gui et al (2021) found that there is a high demand for cooling in the summer but little demand for heating in the winter in the energy consumption of academic buildings at Griffith University, Australia. Moreover, occupant presence in buildings may significantly reduce the overall energy consumption of buildings.…”
Section: Introductionmentioning
confidence: 99%